Contextualizing Community Economic Development - Ahmad Gamal (International Journal of Built Environment and Scientific Research, 2018)
This paper is aimed at contextualizing the approach of Community Based Development as an alternative solution of communities to reduce dependency to the outer forces. It is conducted by examining a heavily urbanized area in Central Jakarta and to compare it with different scales of contexts. Kelurahan Cideng has very unique context since its urban environment has particular population composition of the dichotomic extremes: the poor and the rich as well as those involved in formal and informal employment. The study treats a national government’s policy of the integration of Posyandu, BKK and provincial initiative of PAUD as the interplay with the socio-economic context of Cideng.